Mycorrhizal Phosphorus Efficiencies and Microbial Competition Drive Root P Uptake - Clausing, Simon; Polle, Andrea (Frontiers in Forests and Global Change, 2020)
Phosphorus (P) availability shows large differences among different soil types, affecting P nutrition of forest trees. Chemical binding of P to soil moieties affects partitioning of P between soil particles and solution, influencing soluble P concentrations upon which plants, their associated mycorrhizal symbionts, and microbes feed. The goal of this study was to characterize root P uptake by mycorrhizal and non-mycorrhizal root tips in competition with microbes in situ in the organic and mineral layer of a P-rich and a P-poor forest. We used intact soil cores (0.2m depth) from beech (Fagus sylvatica) forests to tracing the fate of 33P in soil, plant and microbial fractions. We used the dilution of 33P in the rhizosphere of each soil layer to estimate the enrichment with new P in mycorrhizal and non-mycorrhizal root tips and root P uptake. In soil cores from P-rich conditions, 25% and 75% of root P uptake occurred in the organic and mineral layer, respectively, whereas in the P-poor forest, 60% occurred in the organic and 40% in the mineral layer. Mycorrhizal P efficiency, determined as enrichment of new P in mycorrhizal root tips, differed between soil layers. Root P uptake was correlated with mycorrhizal P efficiency and root tip abundance but not with root tip abundance as a single factor. This finding underpins the importance of the regulation of mycorrhizal P acquisition for root P supply. The composition of mycorrhizal assemblages differed between forests but not between soil layers. Therefore, differences in P efficiencies resulted from physiological adjustments of the symbionts. Non-mycorrhizal root tips were rare and exhibited lower enrichment with new P than mycorrhizal root tips. Their contribution to root P supply was negligible. Microbes were strong competitors for P in P-poor but not in P-rich soil. Understory roots were present in the P-rich soil but did not compete for P. Our results uncover regulation of mycorrhizal P efficiencies and highlight the complexity of biotic and abiotic factors that govern P supply to trees in forest ecosystems.